Sifat Mekanis Bahan Kayu pada Rumah Tradisional Batak Karo (Mechanical Properties of Timber Materials on Batak Karo Traditional House) - F. Dona Artha; Yulianto P Prihatmaji (Jurnal Ilmu dan Teknologi Kayu Tropis, 2019)
Batak Karo Traditional House in North Sumatra, known as Siwaluh Jabu used pengki (Ulmus lanceifolia), ingul (Toona sureni), haudolok (Syzygium sp.), and simartolu (Schima sp.) woods. Evaluation mechanical properties of wood with compression, three-point bending, four point bending, and four point shear test was performed to determine the compressive strength, MOR, shear strength, MOE, and  shear modulus (G). To determine the differences of mechanical properties between Batak Karo and Java wood, teakwood (Tectona grandis) and Jackfruit wood (Artocarpus heterophyllus) are selected as a control specimen. The value of MOE and yield stress have strong relationship with density. The higher the density resulted in the higher MOE and yield stress. MOE, MOR, and G in the bending test have not strong relationship with density. The value of MOR and G, teakwood from Java has similar mechanical properties to pengki wood, while nangka (Artocarpus heterophyllus) wood has similar mechanical properties to haudolok wood. Shear strength  has a weak relationship with the density. In terms of shear strength, teak wood has similar mechanical properties to pengki wood, while nangka wood has similar mechanical properties to haudolok wood.